2022
DOI: 10.3390/tropicalmed7100281
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Effect of Amikacin and Imipenem Combinations against Multidrug-Resistant E. coli

Abstract: Introduction: The emergence of multidrug-resistant (MDR) E. coli has developed worldwide; therefore, the use of antibiotic combinations may be an effective strategy to target resistant bacteria and fight life-threatening infections. The current study was performed to evaluate the in vitro and in vivo efficacy of amikacin and imipenem alone and in combination against multidrug-resistant E. coli. Methods: The combination treatment was assessed in vitro using a checkerboard technique and time-killing curve and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Similar to our study, Sara et al have suggested that imipenem is effective in the treatment and control of serious infections caused by MDR E. coli and in the reduction of bacterial resistance emergence. 31 As healthcare providers play a pivotal role in patient care, their understanding and recognition of the evolving patterns of antibiotic resistance are essential in guiding appropriate treatment decisions. Monitoring the prevalence of ESBL-producing E. coli infections in pediatric patients can offer valuable insights into the local and regional antimicrobial resistance trends, helping healthcare professionals make informed choices when prescribing antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, Sara et al have suggested that imipenem is effective in the treatment and control of serious infections caused by MDR E. coli and in the reduction of bacterial resistance emergence. 31 As healthcare providers play a pivotal role in patient care, their understanding and recognition of the evolving patterns of antibiotic resistance are essential in guiding appropriate treatment decisions. Monitoring the prevalence of ESBL-producing E. coli infections in pediatric patients can offer valuable insights into the local and regional antimicrobial resistance trends, helping healthcare professionals make informed choices when prescribing antibiotics.…”
Section: Discussionmentioning
confidence: 99%